Analisis Perilaku Lesbian dalam Perspektif BK Islami - Mei Yulianti, Eva; Pramudia Trisnani, Rischa; Ariswanti Triningtyas, Diana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Adolescent same-sex attraction has led to negative behaviors and challenges among adolescents, particularly in Bulu Village. The emergence of lesbianism in this community indicates a departure from societal norms regarding sexuality, causing intimidation and issues within the local populace. This study concentrates on integrating Islamic values and counseling into the attitudes of LGBT groups, particularly junior and senior high school students. Using a qualitative approach, the research took place in Bulu Village over four months during the 2021/2022 academic year. Primary data came from interviews and observations, while secondary data were derived from documentation. The findings reveal that respondents' deviant sexual orientation falls into the moderately deviant category. They experience attraction to the same sex and even engage in romantic relationships. An Islamic perspective aims to guide these individuals in changing their attitudes, assisting those struggling with sexual orientation and lesbian viewpoints. Challenges faced by respondents include managing daily life and avoiding deviant behavior. Strategies include acknowledging wrongdoing, seeking repentance, avoiding negative influences, and maintaining positivity.